Card Media Development Truth or Dare for Class IV Science and Technology Subjects at UPT SDN 023 Pandau Jaya - Annisa, Nurul; Mustika, Dea (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to develop Truth or Dare card learning media and assess its feasibility as well as the response of IV students at UPT SDN 023 Pandau Jaya to science learning. Research and development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data collection instruments used are: Interviews, validation sheets, and questionnaires were used to collect data from teachers and students. The validation results obtained were 87.5% from material experts, 100% from media experts, and 94% from language experts. Based on limited test responses students produced an average of 91.6%. The practicality assessed by the class teacher resulted in an average score of 94% which is included in the